Heterogenous MSH6 Loss Is a Result of Microsatellite Instability Within MSH6 and Occurs in Sporadic and Hereditary Colorectal and Endometrial Carcinomas. (October 2015) - Graham, Rondell P.; Kerr, Sarah E.; Butz, Malinda L.; Thibodeau, Stephen N.; Halling, Kevin C.; Smyrk, Thomas C.; Dina, Michelle A.; Waugh, Victoria M.; Rumilla, Kandelaria M.
<x xml:space="preserve">Abstract</x> Mismatch-repair (MMR) immunohistochemistry is used to detect tumor MMR deficiency associated with high-level microsatellite instability (MSI). Rare tumors show heterogenous loss of mutS homolog 6 (MSH6) with immunohistochemistry, defined by areas of retained staining and separate areas of complete loss of staining. To investigate the clinical interpretation of this phenomenon, we identified 22 cases of heterogenous MSH6 loss interpreted at Mayo Clinic from January 2001 through December 2012 and reviewed histologic features, MSH6 and other MMR immunohistochemistry, and accompanying MSI testing results (n=20). Heterogenous MSH6 loss was seen in colorectal carcinoma (n=18), endometrial carcinoma (n=3), and sebaceous neoplasm (n=1). In the 18 colorectal carcinoma cases, it accompanied complete loss of mutL homolog 1 (MLH1) or PMS2, or both. Heterogenous MSH6 loss was characterized by MSI and MSH6 C8 tract instability in treatment-naive cases and showed mucinous or signet-ring zones in one quarter of cases. Two cases status post neoadjuvant chemoradiation showed heterogenous MSH6 loss but were microsatellite and C8 tract stable. C8 tracts were unstable in 2 of 4 MSH6-associated Lynch syndrome (LS) tumors, but all 4 showed complete MSH6 loss on immunohistochemistry. Further, 12 such MSH6-associated LS cases showed complete MSH6 loss. In conclusion, heterogenous MSH6 loss is uncommon, usually caused by instability in MSH6 exon 5 polycytosine tract, and not associated with germline MSH6 mutation. Although heterogenous MSH6 loss provides evidence against germline MSH6 mutation, patients whose tumors exhibit this immunolabeling pattern may have LS due to a defect in a different MMR gene.